Geoinformation modeling of selection of territories for non-agricultural use - Moskalenko, A.; Zakharova, A. (Land Management, Cadastre and Land Monitoring, 2021)
Possibilities of application of geoinformation modelling for the selection of land plots of non-agricultural purpose are considered. An analysis of the state of the study of issues related to the automation of decision support and the use of geographic information support for environmental issues. The use of geoinformation modelling for the selection of non-agricultural land plots is considered.This study describes the structuring of the general algorithm for establishing the necessary and impossible locations of objects and their limitations through a functional model. The functional model of site selection is generally common, i.e.: it is necessary to determine the desired location and exclude areas with restrictions, but for each object, it is necessary to set restrictions based on the environment. The article analyses the requirements for the selection of areas for two types of facilities: filling station and disposal tip. Geoinformation models of a selection of non-agricultural land plots for the placement of certain objects have been developed and implemented.As a result of this work, it is determined that the selection of land for the location of some non-agricultural facilities can use an algorithm that allows you to automate some stages of determining the territory.The results of the work can be used in community planning to form spatial decisions on the use of non-agricultural facilities.Key words: geoinformation modeling, model, selection of territories, geoimage.